Cross-border cooperation as a key element of internal security – selected aspects - Ireneusz Fabia; Urszula Fabia; Sebastian Piotrowski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The Cross-border cooperation has become an essential element of internal security in an increasingly globalized and interconnected world. Contemporary challenges such as transnational organized crime, terrorism, cyber threats, and migration require states to engage in collaborative frameworks that transcend traditional territorial boundaries. This article explores the theoretical foundations of cross-border cooperation, emphasizing its role in addressing internal security threats. Drawing upon theories such as functionalism and regionalism, the paper highlights how shared interests and mutual benefits drive cross-border collaboration. The study discusses the practical dimensions of cooperation, focusing on areas such as data-sharing, joint law enforcement operations, and disaster response mechanisms. It also examines the pivotal role of initiatives like the Schengen Information System, Europol, and regional cross-border frameworks such as Euroregions. Despite its successes, cross-border cooperation faces significant challenges, including political and legal barriers, technological disparities, and social mistrust